Identifying the target groups for the educational outreach to reduce BBAs in Mangaung - Dywili, Sidney (University of the Free State, 2018)
The purpose of this study was to investigate the causes of births before arrival (BBAs) in order to identify the target groups for educational outreach programmes to reduce the number of births before arrival (BBAs) at the health facilities in the Mangaung area. The researcher purported to establish the following: i. Local causes or contributing factors leading to BBAs in the Mangaung area. ii. Recommendations for the educational outreach for target groups to reduce BBAs and hopefully prevent unnecessary loss of life. The following causes were distinct: There was a great delay in calling for transportation from the time labour pains started. Some of the BBA participants were found to have had a precipitous labour and as a result they had a much shorter labour period. BBA participants lacked knowledge and insight about pregnancy/labour, signs and symptoms of the onset of labour as well as its complications and others did not know their gestation period. Delayed ambulance transportation led to births occurring before arrival at the health facility. The target groups for the educational outreach on BBAs in Mangaung were established as the following: The ambulance personnel including the dispatch or call centre team (to address call priorities); the antenatal health care personnel (so as to educate pregnant mothers continuously during the ANC visits); and the pregnant mother or patient (including women in child bearing age, those who wish to get pregnant and their support structures). The following were established as common outcomes of BBAs in Mangaung: there were more pre-term births from the BBA participants; and BBA participants had more adverse outcomes, like hypotension, uterine inversion, or placental retention. The second objective concerned establishing the contributing factors leading to mothers ending up with BBAs in the Mangaung area. These were found to be multiparity, distance from the healthcare facility (to reach it in time to deliver the baby in this safe environment), the mother’s level of education, whether the mother had attended antenatal clinic; the level of social support which the mother experienced; and her preparation for labour. The objective of the study was to identify the target groups for the educational outreach to reduce BBAs in Mangaung. The study confirmed that BBAs are at high risk of continuously occurring if education is not addressed and mitigating strategies are not put in place to address the problem. Recommendations on these steps are offered to address the problem of education of the target groups.
Dissertation (M.HPE (Health Professions Education))--University of the Free State, 2018
Keywords: Births before arrival (BBAs); Educational outreach programmes; Mangaung; Free State; South Africa; Causes; Contributing factors